Evaluation of Sample Handling Effects on Serum Vitamin E and Cholesterol Concentrations in Alpacas. (12th January 2014) - Lear, Andrea S.; Byers, Stacey R.; Callan, Robert J.; McArt, Jessica A. A.
Abstract : Clinical cases of vitamin E deficiencies have been diagnosed in camelids and may indicate that these species are more sensitive to inadequate vitamin E in hay-based diets compared to other ruminant and equine species. In bovine, cholesterol has been reported to affect vitamin E concentrations. In order to evaluate vitamin E deficiencies in camelids, the effects of collection and storage of the blood samples prior to processing were necessary. Reports vary as to factors affecting vitamin E and cholesterol in blood samples, and diagnostic laboratories vary in instructions regarding sample handling. Blood was collected from healthy alpacas and processed under conditions including exposure to fluorescent light, serum and red blood cell contact, tube stopper contact, temperature, and hemolysis. Serum vitamin E and cholesterol concentrations were then measured. Statistical analyses found that the vitamin E concentrations decreased with prolonged contact with the tube stopper and with increasing hemolysis. Vitamin E concentration variations were seen with other factors but were not significant. Time prior to serum separation and individual animal variation was found to alter cholesterol concentrations within the sample, yet this finding was clinically unremarkable. No correlation was seen between vitamin E and cholesterol concentration, possibly due to lack of variation of cholesterol.